The deliverance of open access books Examining usage and dissemination - Snijder, Ronald (Amsterdam University Press, 2019)
In many scholarly disciplines, books - not articles - are the norm. As print runs become smaller, the question arises whether publishing monographs in open access helps to make their contents globally accessible. To answer this question, the results of multiple studies on the usage of open access books are presented. The research focuses on three areas: economic viability; optimization of open access monographs infrastructure and measuring the effects of open access in terms of scholarly impact and societal influence. Each chapter reviews a different aspect: book sales, digital dissemination, open licenses, user communities, measuring usage, developing countries and the effects on citations and social media.